ANALISIS YURIDIS KETENTUAN PRESIDENTIAL THRESHOLD BERDASARKAN UNDANG-UNDANG NOMOR 42 TAHUN 2008 TENTANG PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN - Fitra, Ade Fadillah; Haryono, Dodi; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Disclose information is a kind of democracy that can be realized as people right as form of acknowledgement to human right and is a kind of goverment accountable to the people. Historically, the birth of reformation in Indonesia brough the spirit of revolution in every part of goverment’s system, including revolution to open all accesses information from goverment that previously is closed and manipulated. With birth of law No. 14 year 2008 and the formed of committee of information in Indonesia is expected to be a forum for people as a warranty to get the right of getting information, claim for goverment to open all accesses information, and provider of information to public.However, the implementation of task and authority of the commission of information still have many weaknesses. In the fifth year, the commission of information still didn’t have any action that give contribution to make a good system of goverment, honest, accountable, and away from corruption, collusion, and nepotism in Indonesia.Keywords : Commission of information , authority , law No. 14 year 2008